TIPOLOGI KAUSATIF FORMAL BAHASA JAWA KUNA - Ni Ketut Ratna Erawati (Fakultas Sastra Universitas Negeri Malang, 2014)
The old Javanese language (OJL) is a language with rich morphemes that form words. This implicates the syntactic process in the language. One example of a syntactic alternation is a causative. Causative is a valence-raising mechanism in the structure of a clause. This study aims to describe the formal causative in OJL. Causative in OJL is morphologically marked on the verb. Causative verbs can be formed from non-causative ones, such as adjectives and basic verbs. In OJL there are three types of causative: morphological, lexical and analytic causative. Morphological causative is formed by affixes like mang- / ng+-i , paha-+-in-, -um-+-akên (a), infix - um-, and -in- / -an, -in- ( in the passive voice). Lexical causative is the basic form which has a causative meaning. Analytic causative is formed by adding a verb form gawe, matangyan, and hetu. Intransitive verb clause is diathesis patientive. The transitive verb clause has two macro roles, namely actor and undergoer. When the two macro situations are merged into a single macro situation, the particles are connected by conjunctions: sawet, matangyan, apan, and karana